Welcome to the ZEB REVOlution - Cadge, Stuart (GEOmedia, 2016)
GeoSLAM is a manufacturer and supplier of handheld, 3D mobile mapping systems. Founded in 2012 and headquartered in the UK, GeoSLAM now has a global distribution network of 35 distributors across six continents.